Muraqabah as the Internalization of the Hawthorne Effect in Islamic Transpersonal Psychology: Muraqabah as the Internalization of the Hawthorne Effect in Islamic Transpersonal Psychology - Al Afify, Muhamad Faiz (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2025)
This study aims to determine whether or not there is a connection between the Hawthorne effect, which describes the tendency of individuals to change their behavior when they feel that they are being monitored, and the Sufi concept of muraqabah, which describes the spiritual comprehension of being viewed by Allah. The purpose of this study is to determine whether or not there is a connection between the two. On the other hand, contemporary psychology focuses an emphasis on outward observation as a behavioral stimulant, but Sufism encourages interior, divine awareness as a type of self-purification. Sufism is a faith that was developed in the Middle East. This study employs a qualitative hermeneutic and transdisciplinary method in order to provide an explanation for muraqabah, which is defined as the absorption and transcendence of the Hawthorne effect within the context of Islamic spirituality. Muraqabah appears to be a more credible and authentic method to the process of self-transformation, according to the findings of the study. The examination of society is not the basis for this method; rather, it is predicated on a continuous divine consciousness. Developing more comprehensive and spiritually grounded forms of Islamic psychotherapy is achievable via the merging of Sufi principles with Islamic transpersonal psychology. This opens up new options for the development of Islamic psychotherapy